2003
DOI: 10.1007/978-3-540-40014-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Out-of-Core Visualisation of Very Large Landscapes on Commodity Graphics Platform

Abstract: Abstract.We recently introduced an efficient technique for out-of-core rendering and management of large textured landscapes. The technique, called Batched Dynamic Adaptive Meshes (BDAM), is based on a paired tree structure: a tiled quadtree for texture data and a pair of bintrees of small triangular patches for the geometry. These small patches are TINs that are constructed and optimized off-line with high quality simplification and tristripping algorithms. Hierarchical view frustum culling and view-dependend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The precision for each class is de ned as È Ê AE (4) First of all we verify the validity of the two criteria: the moment of the color and the edge energy based on the anisotropic diffusion. The feature vectors in our method are compared with features that are often used for general image retrieval [8,10]: Table 1 shows the comparison in color.…”
Section: Precision Of Classi Cationmentioning
confidence: 98%
See 1 more Smart Citation
“…The precision for each class is de ned as È Ê AE (4) First of all we verify the validity of the two criteria: the moment of the color and the edge energy based on the anisotropic diffusion. The feature vectors in our method are compared with features that are often used for general image retrieval [8,10]: Table 1 shows the comparison in color.…”
Section: Precision Of Classi Cationmentioning
confidence: 98%
“…Since the data in the 3D map mostly consist of many small, already simpli ed meshes (like buildings made of some cuboids), these simpli cation methods, in which they assume that a single mesh contains a large number of vertices, cannot be applied to it. Although some methods on modeling and rendering of the 3D maps have been already proposed [4][5][6], there exist few methods concerning the reduction of the texture data for the 3D map. In the 3D map, the proportion of the volume of data in texture tends to be much higher than that of geometrical information such as vertices and triangles.…”
Section: Introductionmentioning
confidence: 99%
“…Cignoni et al [3], [4], [5] have demonstrated the ability to display both adaptive geometry and texture of large terrain data sets in real-time. They utilize a quadtree texture hierarchy and a bintree of triangle patches (TINs) for the geometry.…”
Section: Related Workmentioning
confidence: 99%
“…With management of large textured landscapes, [19] can realize the visualization of very large models on commodity graphics platforms. Moreover, out-of-core algorithms were also employed in other fields, such as mesh simplification for large complex models [20].…”
Section: Out-of-core Techniquesmentioning
confidence: 99%